Academician Ivan Gams and his influence on development of geomorphology in the Republic of Croatia - Bognar, Andrija (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The author presents the role of academician Ivan Gams in the reorientation and modernization of Croatian geomorphology during 1970's and 1980's. The causes for losing contact with contemporary development of geomorphology in the world are analyzed in detail, and the way of reestablishing the former reputation and importance of Croatian geomorphology is presented, especially through the implementation of detailed geomorphological mapping, new methods of geomorphological investigation and education of younger scientific personnel at the university of Zagreb.
Keywords: Croatia; Gams, Ivan, 1923-; geomorfologija; geomorphology; Hrvaška; krasoslovje; slovenski geografi